Komunikasi Pemasaran Terpadu Bioskop Moviplex Pasca Covid 19 di Kota Sukabumi - Muhamad Randi Paisal (Jurnalika : Jurnal Ilmu Komunikasi, 2025)
With the development of the film industry and increasing competition in the entertainment sector, cinemas are required to innovate in marketing strategies in order to attract and retain customers. The aim of this research is to determine the advertising, personal selling, sales promotion, publicity and direct marketing carried out by cinemas. Moviplex, refers to the Integrated Marketing Communication theory of Kotler and Armstrong. This research uses a qualitative approach with descriptive methods, this research was conducted at the Moviplex Cinema. There were 4 informants consisting of 1 Moviplex Cinema manager, 1 marketing person and 2 people in the audience using purposive sampling technique. Data collection through structured interviews, unstructured observations with the following tools; interview guide and gadgets. Data validation uses triangulation (Source, Technique and Time) and is analyzed by data reduction, data presentation and verification. The results of the research that has been carried out show that the Integrated Marketing Communication carried out by Moviplex Cinemas has been achieved because advertising has been carried out well, personal sales have been carried out efficiently, sales promotions have been carried out optimally, publicity has been packaged attractively, direct marketing has been carried out consistently and sustainably.